(untitled) (Docentes 2.0 Journal, 2024)
Science and technology are part of the tools that we cannot do without in the 21st century. The main objective was to analyze education and its role in society from the perspective of how it generates improvements in GDP per capita and how educational quality is not a false promise and illusion. Mathematics in operations research, such as queuing theory and game theory, was used as a paradigm. The population was students and workers from Argentina and Spain, taking case studies from those countries as samples. In addition, a technological approach with the same mathematical instruments as the original models is needed. The hypotheses were demonstrated with samples taken from a population of students and workers from Argentina and Spain. The results were conclusive in knowing that quality education generates greater monetary and other gains in people, raising better educational policies as a discussion and concluding that education begins in the family. An important part of the article is the analysis of the life cycle of systems to conclude on systemic education.